Forest-to-pasture conversion in the Eastern Amazon: impacts on the soil methane microbial communities - Venturini, Andressa Monteiro (2019)
Forest-to-pasture conversion in the Amazon alters the physical, chemical, and biological properties of the soil. However, the impacts of this process on the methane (CH4) fluxes - the second most important greenhouse gas of anthropogenic origin - and microorganisms responsible for its production (methanogenic Archaea) and consumption (methanotrophic Bacteria) from soils are still little known. Both groups can also be influenced by the moisture content of these soils, due to the seasonality and occurrence of extreme events in the region. Therefore, the objective of this thesis was to evaluate the impacts of forest-to-pasture conversion on the microbial CH4 cycle in soils of the Tapajós National Forest and its surroundings, in the Brazilian Eastern Amazon, as well as its response to changes in moisture. In the first study, soil samples were collected in three forests and three pastures during the dry and rainy seasons. In the second, soil samples from both land-uses were used in the development of a microcosm experiment with four moisture levels (original moisture; 60%, 80%, and 100% of moisture at field capacity) for a 30-day period. The soil samples from both studies had their properties determined, whereas their microbial communities were evaluated by quantitative real-time PCR of CH4 marker genes and metagenomic sequencing. Gas samples from the microcosm experiment were also periodically collected and analyzed by gas chromatography. As main results, the pastures had a higher pH and nutrient levels than the forests, but the field samples revealed a decrease in porosity and an increase in soil density. This has led to changes in the diversity, evenness, and abundance of the CH4 microbial communities, composed by methanogenic organisms of the phylum Euryarchaeota and methanotrophs of the phyla Proteobacteria and Verrucomicrobia. Pastures consistently showed a greater abundance of methanogens than forests, as well as a higher rate of methanogens by methanotrophs, usually close to or above one. Moisture further intensified this effect, resulting in high CH4 emissions from the soils of the experiment under 100% of moisture at field capacity. The main methanotrophic groups exhibited different responses to the studied factors, according to their ecological characteristics. In summary, the data from both studies indicate that forest-to-pasture conversion increases the CH4 emission potential of the soil, which is enhanced by increasing moisture